Crystal structure of 3-[(4-phenylpiperidin-1-yl)methyl]-5-(thiophen-2-yl)-2,3-dihydro-1,3,4- oxadiazole-2-thione, C18H19N3OS2 - Al-Wahaibi Lamya H.; Blacque Olivier; Tiekink Edward R.T.; El-Emam Ali A. (Zeitschrift für Kristallographie - New Crystal Structures)
C18H19N3OS2, orthorhombic, Pca21 (no. 29), a = 14.8852(2) Å, b = 5.23480(10) Å, c = 44.1008(7) Å, V = 3436.38(10) Å3, Z = 8, R gt(F) = 0.0554, wR ref(F 2) = 0.1501, T = 160 K.